Residensi Kepemimpinan dan Manajemen Keperawatan di Instalasi Gawat Darurat Rumah Sakit Advent Bandung - HamonanganTambunan; Silalahi, Harlena; Daniel Shandy (Yayasan Literasi Sains Indonesia, 2025)
This nursing leadership and management residency proposal in the Emergency Department (IGD) of Adventist Hospital Bandung aims to improve the competence of nurses in providing optimal emergency services. This study analyzes the problems faced by ER nurses, namely lack of training and delays in handling non-emergency patients. A SWOT analysis was conducted to identify the strengths, weaknesses, opportunities, and threats faced. Based on the SWOT analysis, this study proposes several strategies, including: (1) improving nurse competence through ongoing training, (2) improving nurse welfare, (3) improving resources and facilities, (4) improving team collaboration, (5) developing policies and practice standards, (6) evaluating and monitoring performance, (7) improving knowledge and technology, (8) improving ongoing training programs. In addition, this study also proposes a solution to overcome delays in handling non-emergency patients, namely by developing and managing urgent care. This study is expected to provide a positive contribution in improving nurse competence and the quality of health services in the ER of Adventist Hospital Bandung. Data were collected through participant observation of the implementation of residency activities, semi-structured interviews with 10 nursing residents and 5 emergency room heads, and documentation studies in the form of residency guidelines and resident performance evaluations. Qualitative data from interviews were analyzed using thematic analysis techniques, while quantitative data from observations were analyzed descriptively. The results of the SWOT analysis showed that the strength of the residency lies in the quality of education and support from the hospital.